Koperasi Jasa Keuangan Syariah Studi tentang Aspek-aspek Yuridis Permodalan di BMT Al Fallah Klaten - Putrianasari, Giffari, Kelik Wardiono, S.H., M.H, Inayah, S.H., M.H (2015)
Cooperative is a financial institution that is in demand by the people of Indonesia. Kinship principle in it became a separate option for the people of Indonesia. Cooperative forms of capital must be understood, after the capital will be visible understand how the position of Cooperative Members. In addition there is a cooperative similar to BMT but sharia-based cooperative. This study was based on doctrinal research with this type of research discovery Concreto In- Law, the object of study is the AD/ART BMT Al - Fallah Klaten. Capital AD/ART BMT Al - Fallah Klaten there are some aspects of the Subject, Object, rights and obligations of the parties in accordance/not in accordance with Act No. 25 of 1992 concerning Cooperatives as well as Islamic law. So there is a difference Position of the BMT Al - Fallah Klaten.